Morphological and ontogenetic studies with inflorescences and flowers of Lepidagathis Willd. (Acanthaceae) - Hirao, Yasmin Vidal (2015)
The phylogeny of Acanthaceae, chiefly based on molecular data, confirms the monophyly of the family, however, a morphological synapomorphy to characterize it is still unknown. Apart from being well represented in our flora, the identification of its species is quite difficult due to taxonomic problems and lack of morphological studies. The family presents many morphological instabilities within genera, for example with the pattern of inflorescences. Lepidagathis Willd. serves as an example, presenting three types of inflorescence and divergent floral morphologies that have challenged its systematics. Therefore, exploring the morphology, anatomy, vascularization and development of the inflorescence and flowers, it was possible to find homologies between the studied species and speculate around its evolution. The patterns of the inflorescence were discovered to be enriched or depleted forms of the same architecture. On some species, there were more or less reproductive meristems on the axil of bracts, and therefore, more or less possibilities of developing flowers or partial inflorescences. The available phylogeny for the group suggests an equal probability of gain or loss of such reproductive meristems on the inflorescences. The development of the floral whorls on the studied species was the same, despite their different external morphology. Nevertheless, the vascularization of the flowers revealed important aspects of the floral evolution of the genus, showing that the anatomy may retain ancestral characteristics that relate the species. Thus, the display and volume of flowers of each inflorescence, and the size and arrangement of the flowers are more likely related to the pollination syndromes of each species. The results corroborate the current circumscription of Lepidagathis and encourages further investigations with Acanthaceae species that may lead to interesting discoveries on homologies and assist the phylogenetic studies with the family